[Man and three children in garden]
Portrait of man in three piece suit standing in garden with two boys and one girl with her teddy.
Same man and garden as with previous item, probably taken on the same day.
Keywords: Ireland -- History -- 1922-; Photographic prints -- Irish -- 1920-1940